Carotid Rupture during Stent-Assisted Aneurysm Treatment - Wada, Hajime; Piotin, Michel; Boissonnet, Hervé; Spelle, Laurent; Mounayer, Charbel; Moret, Jacques (American Journal of Neuroradiology, 2004)
Summary: We report the case of a supraclinoid carotid rupture during the delivery of a balloon-expandable stent in a 59-year-old patient with incidental paraclinoid berry aneurysms for whom stent-assisted coiling was planned. The deployment of the stent resulted in immediate rupture of the artery. We describe the emergent management of this complication with prolonged balloon inflation to occlude the site of rupture, a treatment that led to the discharge of the patient 2 weeks later without any sequelae.